Dynamics of Germination and Growth and Development of Cotton Variety Termiz-202 with Thin Fiber - Qodirov Axmadjon Abduraufovich; Sayyora Roziqlovna Boynazarova; Ibroximova Fotima Sobirjonning qizi (Scientific Trends, 2022)
The germination dynamics, growth and development of fine-fiber Termiz -202 cotton, grown in the soil and climate conditions of Surkhandarya region, are described.
Keywords: fine fiber Termiz-202 new tuber, germination, seedling, seedling